Specific Membranous Structures Associated with the Replication of Group A Arboviruses - Grimley, Philip M. (1972)
Intracytoplasmic membranous structures of a unique type were associated with the replication of three group A arboviruses: Semliki Forest virus (SFV), Sindbis virus, or Western equine encephalomyelitis virus. The structures, referred to as type 1 cytopathic vacuoles (CPV-1), were membrane-limited and characteristically lined by regular membranous spherules measuring 50 nm in diameter. The membranous spherules typically contained a fine central density, but were neither virus cores nor virions. Detection of CPV-1 by electron microscopy at 3 to 6 hr postinfection coincided with the time of rapid virus growth and preceded the accumulation of virus nucleocapsids. A range of 20 to 100 CPV-1 profiles were counted per 100 ultrathin cell sections at 6 to 9 hr postinfection when viruses were grown in chick embryo, baby hamster kidney, or mouse L cells. Maximum counts remained in the same range even when the multiplicity of infection was varied over 100-fold. Inhibition of cellular ribonucleic acid (RNA) and protein synthesis by actinomycin D during SFV infection did not decrease the counts of CPV-1; however, biogenesis of CPV-1 was decreased when viral replication was limited by inhibitors of viral RNA synthesis (guanidine) or of viral protein synthesis (cycloheximide). On the basis of present and earlier findings, we concluded that formation of CPV-1 must result from a virus-specified modification of pre-existing host cell macromolecules.